Pengaruh Literasi Keuangan dan Faktor Demografis terhadap Keputusan Investasi pada Masyarakat Surabaya - Faradinah Febriyanti; Muazaroh Muazaroh (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
Investment decisions are decisions or policies taken by someone to invest capital in assets that are expected to generate profits in the future.Financial literacy is a person's ability to make decisions and manage finances wisely, which starts with knowing and understanding financial management for a better future. Income is income received by a person in the form of salary, sales proceeds, investment or other funds. Education level is the higher a person's education level, the more financial literacy is reflected and the more likely investors are to invest part of their funds in riskier capital market instruments than relatively safe banking instruments. The number of respondents from this study were 120 respondents who came from the Surabaya City area with the distinction of having investments in various assets and then being more than 20 years old and earning more than four million. Respondents were selected by means of purposive sampling. The data analysis technique used is Partial Least Square Equation Modeling using the Smart-PLS 4.0 program. The results of this study prove that financial literacy has a significant positive effect on investment decisions in the people of Surabaya.